Paraguay : 2013 Article IV Consultation-Staff Report; Press Release. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2013 Article IV consultation highlights the main challenge ahead for Paraguay, which is to improve social and economic development while strengthening the macroeconomic policy framework to cement strong fundamentals. Paraguay's outlook for 2014-18 is favorable, with broadly balanced risks, despite less buoyant external conditions. The economy is expected to continue to be one of the most dynamic in the region, with growth returning to potential of about 4.5 percent a year by 2016, inflation in line with the central bank's target rate, and small fiscal and current account deficits. Consistent with this outlook, the policy stance should be tightened in the near term, with policies guided by fiscal responsibility and incipient inflation-targeting frameworks over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet